LEGAL MEASURES TO PREVENT MONEY LAUNDERING THROUGH ENTITIES - Suwanmanee, Natthanan; Lurang, Radchada (Journal of MCU Social Science Review, 2024)
Objectives of this research article were: 1. To study theoretical concepts. Factual and legal problems, foreign and Thai legal measures regarding money laundering through juristic persons, 2. To study problems and facts and laws of money laundry through entities of Thailand, 3. To study, analyze and compare Thai and foreign legal measurements on money laundry through entities, and 4. To recommend effective legal measures to amend Thai laws appropriately, conducted by the qualitative research by studying documents, legal texts, academic textbooks, research, Thai and foreign electronic media. Focus Group Discussions were organized, containing in-depth interviews with a total of 5 sample groups: who were expert legal professionals Anti-Money Laundering Office Director of the Narcotics Crime Division (DSI), Director of the Screening and Inspection Coordination Division (ONCB), Royal Thai Police Group and Legal Manager of Public Company Limited. The research results found that 1. Money laundering through juristic persons was controlling the establishment of juristic persons that was convenient, fast and not strict in terms of verifying the true beneficiaries. Issuing anonymous share certificates that was contrary to FATF recommendations. 2. Juristic persons with the nature of holding shares on behalf of foreigners. It was not a predicate offense for money laundering. Therefore, cannot be prosecuted for money laundering. 3. The countries that the researcher studied were: United States, Canada, Commonwealth of Australia, Hong Kong Special Administrative Region Swiss Confederation and the Law of the Kingdom of Thailand. All offenses relating to money laundering have been designated as criminal offenses. 4. Money laundering was a criminal offense, and all serious offenses must be designated as money laundering offenses. The intent was to define the primary offense to cover the widest scope.